A novel mutation of Twinkle in Perrault syndrome: A not rare diagnosis?. (12th April 2020) - Gotta, Fabio; Lamp, Merit; Geroldi, Alessandro; Trevisan, Lucia; Origone, Paola; Fugazza, Giuseppina; Fabbri, Sabrina; Nesti, Claudia; Rubegni, Anna; Morani, Federica; Santorelli, Filippo Maria; Bellone, Emilia; et al.
Abstract: Perrault syndrome is a rare disorder characterized by ovarian dysgenesis, bilateral sensorineural hearing loss and associated with mutations in six mitochondrial proteins. Additional neurological features were also described. Herein, we report on a 27‐year‐old woman with Perrault syndrome (PS), moderate ataxia and axonal sensory‐motor peripheral neuropathy in whom we identified compound heterozygous mutations in the TWNK gene (p.Val507Ile and the novel p.Phe248Ser variant). Fewer than 30 patients with PS have been reported worldwide. Neurological involvement is more frequently associated with mutations in TWNK and indicates possible genotype–phenotype correlations. TWNK mutations should be searched in patients with sensory ataxia, early onset bilateral sensorineural hearing loss, and ovarian dysfunction in women.